(untitled) (Public Sector Economics - submission site, 2019)
This article explores the use and added value of the Sustainable Development Goals (SDGs) and indicators in the budgeting process. Several countries have announced in their voluntary national reviews (VNRs) their intention to use the SDGs in their budgetary processes, but few have specified why it would be relevant to do so, or how it could be implemented. Based on nine case studies conducted through interviews, we found that SDG budgeting is still in its infancy. We nevertheless identified four ways in which countries are starting to integrate the SDGs into budgeting processes. Most of the countries we studied either map their budgets against the SDGs or include qualitative reporting in their main budget document. Less often, countries use the SDGs to improve their budget performance evaluation system or as a management tool for resource allocation. Most of the countries follow a technical approach. Only rarely are the SDGs used politically or referenced in the budgetary debate.